2009
DOI: 10.1158/1940-6207.capr-09-0008
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Dietary Energy Restriction in Women at Increased Risk of Breast Cancer

Abstract: Dietary energy restriction (DER) reduces risk of spontaneous mammary cancer in rodents. In humans, DER in premenopausal years seems to reduce risk of postmenopausal breast cancer. Markers of DER are required to develop acceptable DER regimens for breast cancer prevention. We therefore examined markers of DER in the breast, adipose tissue, and serum.Nineteen overweight or obese women at moderately increased risk of breast cancer (lifetime risk, 1 in 6 to 1 in 3) ages between 35 and 45 were randomly allocated to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 62 publications
4
41
1
Order By: Relevance
“…In contrast, we found moderate weight loss induced significant changes in gene expression profiles in adipose tissue and skeletal muscle, particularly genes that are known as CR targets in adipose tissue, identified in previous microarray studies conducted in human subjects (Capel et al, 2008; Johansson et al, 2012; Kolehmainen et al, 2008; Ong et al, 2009; Viguerie et al, 2005). However, data from several studies conducted in rodent models have found many putative resveratrol targets, such as Sirt1, Nampt, and Pgc-1α , are affected by fasting (Hayashida et al, 2010; Yang et al, 2007; Yoon et al, 2001), so it is possible that collecting tissue samples from our subjects after they fasted overnight (~12 h) masked an effect induced by resveratrol on tissue gene expression.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In contrast, we found moderate weight loss induced significant changes in gene expression profiles in adipose tissue and skeletal muscle, particularly genes that are known as CR targets in adipose tissue, identified in previous microarray studies conducted in human subjects (Capel et al, 2008; Johansson et al, 2012; Kolehmainen et al, 2008; Ong et al, 2009; Viguerie et al, 2005). However, data from several studies conducted in rodent models have found many putative resveratrol targets, such as Sirt1, Nampt, and Pgc-1α , are affected by fasting (Hayashida et al, 2010; Yang et al, 2007; Yoon et al, 2001), so it is possible that collecting tissue samples from our subjects after they fasted overnight (~12 h) masked an effect induced by resveratrol on tissue gene expression.…”
Section: Discussioncontrasting
confidence: 80%
“…Nonetheless, CR-induced moderate weight loss altered adipose tissue gene expression profiles in several CR targets identified previously in human subjects, including up-regulation of Ctep (Johansson et al, 2012) and down-regulation of Leptin (Viguerie et al, 2005), Aldoc (Capel et al, 2008; Johansson et al, 2012; Ong et al, 2009), Abcc6 (Ong et al, 2009), and Ccnd2 (Kolehmainen et al, 2008) (Figure S1). …”
Section: Resultsmentioning
confidence: 71%
“…Several dietary trials have evaluated the effects of LFD and/or LCD interventions on adipokine concentrations (de Luis et al 2007; Bluher et al 2012; Befort et al 2012; Scott et al 2013; Giannopoulou et al 2005; Friedenreich et al 2011; Sacks et al 2009; Davis et al 2009; Foster et al 2003; Samaha et al 2003; Brehm et al 2003; Yancy et al 2004; Shai et al 2008; Bradley et al 2009; Reed et al 2010; Ata et al 2010; Ong et al 2009; Harvie et al 2011), but few have focused on premenopausal women (Reed et al 2010; Ata et al 2010; Ong et al 2009; Harvie et al 2011). In our study, overweight and obese premenopausal women were randomized to a LFD or a LCD plus PA for a period of 52 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Harvie et al 2011) examined the effects of a 6-month trial of intermittent and continuous calorie-restricted diets without exercise among premenopausal women and found that these diets yielded significant reduced leptin (approximately 40%) and increased the A/L ratio (approximately 20%). Another study (Ong et al 2009) examined the effects of a 1-month calorie-restricted intervention (62% carbohydrates, 26% protein, and 12% fat), without exercise, on adipokine concentrations and adipokine expression profiles among overweight and obese premenopausal women. They found that post-intervention adiponectin and leptin concentrations were 3% and 60% lower, respectively (Ong et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The Carbohydrates and Related Biomarkers Study was a randomized, cross-over, feeding study testing the effect of low-and high-GL diets on chronic disease susceptibility biomarkers, including biomarkers of inflammation and adipokines, which have been associated with increased risk of cancer, cardiovascular disease, and other chronic diseases (1,(28)(29)(30). The Carbohydrates and Related Biomarkers Study was conducted between June 2006 and July 2009.…”
Section: Methodsmentioning
confidence: 99%